Treatment - Heath, Iona; Louhiala, Pekka; Saunders, John (London : Rodcliffe Publishing, 2014)
This third volume in the Companion to Medical Humanities series considers the concept of treatment as an active process which produces an outcome, be it effective, inappropriate or inadequate.It invites the reader to examine the relevance of the patients' belief in any given treatment and their confidence in the practitioner. Against a person-centred backdrop, it investigates boundaries, and reflects on the practical demands on a health care system limited in its resources, where the price of choice for one may be the restriction of service for the other. It also questions the supposed contrasts between treatment and cure, redefining the meaning of care in daily practice. It offers inspirational reading for all academics and professionals with an interest in the medical humanities, as well as researchers in philosophy of medicine and medical ethics.
1. On treatmnet and its effects -- 2. Wonderful treatment -- 3. Treatment - a matter bwetween subjects -- 4. Deciding on treatment -- 5. Paternalism, power and autonomy -- 6. Symptoms without disease : territory without a map -- 7. The paradox of placebo - real and sham in medicine -- 8. Considering the alternatives : or, who is the medicine man? -- 9. Boldness and temperance in treatment
Includes bibliographical references and index
Keywords: Communication in medicine; Physician and patient; Therapeutics; Therapeutics; Patients -- psychology; Physician-Patient Relations